Pengaruh Penambahan Air Laut Terhadap Nilai Tegangan Bio Baterai Kulit Semangka (Citrullus Lanatus) - Maria Elisabeth Tambui Yokit; Rahman Rahman; Wahyu Kumala Sari (Universitas Cenderawasih, 2023)
The purpose of this study was to analyze the stress value of a mixture of watermelon rind with mineral water and a mixture of watermelon rind and seawater concerning time. The benefit of this research is to provide information about the stress value of the mixture of watermelon rind with mineral water and to provide information about the stress value of the mixture of watermelon rind and seawater. The method that will be used is experimental by testing its tension using a multimeter. The results obtained in this study are: A mixture of watermelon rind with mineral water produces a voltage value in the range of 568 mV - 4280 mV, but the research data has not shown a pattern. The mixture of watermelon rind with seawater produces a voltage value in the range of 338 mV-4240 mV. At the same time of measurement, the number of cells is proportional to the voltage value. The value of the voltage is inversely proportional to the length of the measurement. Keywords: voltage, watermelon, mineral water, sea waters